Stand-Up Comedy as Media to Improve Students' Speaking Skills in The Second Academic Year of SMA Negeri 1 Sumbul - Tampubolon, Surya Kelana Tua; Sinaga, Nenni Triana; Tampubolon, Sahlan (Continuous Education: Journal of Science and Research, 2023)
A Thesis, English Departement Teacher’s Training Faculty of HKBP Nommensen University This study aims to determine the results of using a communicative approach to improve students’ speaking skills. The researcher conducted the research at SMA Negeri 1 Sumbul. This study was carried out by Experimental quantitative research. The sample of this study was class XI-3 (the experimental class) and class XI-4 (the control class), with a total of 20 students for each group. The research conducted experimental teaching and speaking tests with stand-up comedy personal experience to collect data. The result from this research can be seen as follows: t-coun t> t-table (p = 0.1) with the degree of freedom (df) = 38. This means 6,665 > 1.21 (p=0.1) with df 38. This means that the use of a communicative approach has a significant effect on students’ speaking skills. Using the communicative approach as a teaching method through stand-up comedy in class activities improved students’ speaking skills.